The Effectiveness of Rabies Hunter Game Application on Dog Bite Prevention Among School-Aged Children in Southern Region of Sarawak, Malaysia - Syahrizal Abdul Halim; Rosalia Saimon; Parveen Kaur Sarjeet Singh; Razitasham Safii (USIM Press, 2024)
Vol. 33 No. 3 (2021): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences